Gondolatok a becsületsértés szabálysértési alakzatáról - Gyulay Dániel (A Pázmány Péter Katolikus Egyetem Jog- és Államtudományi Karának Könyvei. Doktorandusz Tanulmányok, 2020)
No. Bhar.84/2014/3. of the Pécsi Ítélőtábla (Pécs Regional Court of Appeal) inspired the exami-nation on the off ence formation of defamation. Grounds for its decision made a distinction be-tween the off ence and the criminal formations of defamation, based on the extent of the particu-lar defamatory expression. Consequently, I made the starting point during my research of whether any similar conclusions had occurred in practice apart from that. Substance of the article deals with the possibility of proving the truth as well as with the analysis of the judicial practice. The latter really surprised me since – contrary to my expectations – quite a few defamation cases were brought before courts making it more diffi cult for them to draw conclusions about their decisions.